Botrytized wines – current perspectives - Magyar I (International Journal of Wine Research, 2016)
Ildikó Magyar, János Soós Department of Oenology, Institute of Viticulture and Oenology, Szent István University, Budapest, Hungary Abstract: Botrytized wines are wine specialties made of overripe grapes infected by Botrytis cinerea with the form “noble rot”. Due to the particular characteristics of the noble rotted grape, these wines (eg, Tokaji Aszú, Sauternes, Trockenbeerenauslese types, etc) have many characteristic features, including higher or lower residual sugar content and unique aroma composition. The technology, biochemistry, and special characteristics of botrytized wines have been researched for a long time. This review outlines the main directions of the current studies, giving a brief overview on the recent findings. Beside the traditional wine types, noble rot is increasingly utilized in making newer sweet wine styles and straw (passito) wines, which generates a series of new interesting experimental results. The fungus–grape interactions during the noble rot, the induced botrytization, the microbial communities of botrytized wines, and the volatile compounds having key roles in the distinct aroma of these wine styles are being focused on in the current studies in this field. Keywords: Botrytis, noble rot, sweet wines, passito wine, aroma